2022
DOI: 10.1088/1361-6579/ac944f
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ActiGraph sampling rate on free-living physical activity measurement in youth

Abstract: ActiGraph sampling frequencies of more than 30 Hz may result in overestimation of activity counts in both children and adults, but research on free-living individuals has not included the range of sampling frequencies used by researchers. Objective: We compared count- and raw-acceleration-based metrics from free-living children and adolescents across a range of sampling frequencies. Approach: Participants (n=445; 10-15 y) wore an ActiGraph accelerometer for at least one 10-h day. Vector Magnitude counts, Mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In a true patient scenario, setting the measurement frequency to 10-20 Hz would extend storage and battery life to at least 1-2 months making it more clinically practical without the need to download logged data before that time. Although the magnitude of acceleration may be reduced at lower sampling frequencies, there appears to be minimal impact on the variability of accelerations (suggesting this algorithm would perform similarly on data collected at lower sampling frequencies [28]. However, this should be confirmed in further research.…”
Section: Discussionmentioning
confidence: 88%
“…In a true patient scenario, setting the measurement frequency to 10-20 Hz would extend storage and battery life to at least 1-2 months making it more clinically practical without the need to download logged data before that time. Although the magnitude of acceleration may be reduced at lower sampling frequencies, there appears to be minimal impact on the variability of accelerations (suggesting this algorithm would perform similarly on data collected at lower sampling frequencies [28]. However, this should be confirmed in further research.…”
Section: Discussionmentioning
confidence: 88%
“…Third point is that the questionnaires of school environment answered by the principals and the sociodemographic questions answered by parents may suffer from memory bias. Fourth point is that the accelerometry data was downloaded at a sampling rate of 80 Hz that could overestimate physical activity in children 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The proprietary nature of the AG counts method is not the only aspect of the summary measure which has been criticized. An intensity leveling off with running above 12 km/hr has been demonstrated with hip-worn devices John et al, 2012), which is not observed with wrist-and ankle-worn devices (LaMunion et al, 2017), changes to firmware (John et al, 2014), and sampling frequency issues (Brond & Arvidsson, 2016;Clevenger et al, 2019Clevenger et al, , 2022Garnotel et al, 2021) has further challenged the use of AG counts, even though this is not directly related to the algorithm per se. Moreover, the units of AG counts have been deemed arbitrary (Chen & Bassett, 2005;Straker & Campbell, 2012), as this is not a unit proposed by the International System of Units (SI).…”
mentioning
confidence: 99%